Vaccine Induced Immune Thrombotic Thrombocytopenia Causing a Severe Form of Cerebral Venous Thrombosis With High Fatality Rate: A Case Series - Wiedmann, Markus; Skattør, Thor; Stray-Pedersen, Arne; Romundstad, Luis; Antal, Ellen-Ann; Marthinsen, Pål Bache; Sørvoll, Ingvild Hausberg; Leiknes Ernstsen, Siw; Lund, Christian G.; Holme, Pål Andre; Johansen, Tonje Okkenhaug; Brunborg, Cathrine; et al. (Frontiers in Neurology, 2021)
During a 2-week period, we have encountered five cases presenting with the combination of cerebral venous thrombosis (CVT), intracerebral hemorrhage and thrombocytopenia. A clinical hallmark was the rapid and severe progression of disease in spite of maximum treatment efforts, resulting in fatal outcome in for 4 out of 5 patients. All cases had received ChAdOx1 nCov-19 vaccine 1–2 weeks earlier and developed a characteristic syndrome thereafter. The rapid progressive clinical course and high fatality rate of CVT in combination with thrombocytopenia in such a cluster and in otherwise healthy adults is a recent phenomenon. Cerebral autopsy findings were those of venous hemorrhagic infarctions and thrombi in dural venous sinuses, including thrombus material apparently rich in thrombocytes, leukocytes and fibrin. Vessel walls were free of inflammation. Extra-cerebral manifestations included leech-like thrombi in large veins, fibrin clots in small venules and scattered hemorrhages on skin and membranes. CVT with thrombocytopenia after adenovirus vectored COVID-19 vaccination is a new clinical syndrome that needs to be recognized by clinicians, is challenging to treat and seems associated with a high mortality rate.